M-health for health behaviour change in resource-limited settings: applications to HIV care and beyond - Thirumurthy, Harsha; Lester, Richard (Bulletin of the World Health Organization, 2012)
Of the new advanced information and communication technologies, cellular telecommunication networks and mobile phones have reached far more people than any other, especially in developing countries. Although Internet use has also increased substantially in recent years, in 2011 26% of the people in developing countries had Internet access, whereas 79% had mobile or cellular phone subscriptions. This landscape of expanded access to modern communication technologies has given rise to the concept of "mobile health" (or m-health, a part of what is commonly referred to as "electronic health" or e-health), which is the use of mobile phones for improving health outcomes. This paper draws on the results of three m-health interventions recently evaluated in Kenya to illustrate health behaviours that are particularly amenable to change through m-health interventions. It also underscores the need for controlled trials and points out those aspects of m-health that require further research. Access to life-saving antiretroviral therapy or people with human immunodeficiency virus infection has increased in parallel with the closing of the divide between developed and developing countries in the use of mobile phones.